Solving the Time-Ahead Pricing of Energy Supply Problem with Nonlinear Utility Function for Consumers via a Bilevel Optimization Approach (2014)
Coppta Team's Technical Report of the 20014 AIMMS-MOPTA Optimization Modeling Competition (http://coral.ise.lehigh.edu/mopta2014/competition/)